'At-risk' places: inequities in the distribution of environmental stressors and prescription rates of mental health medications in Glasgow, Scotland. (30th October 2015) - Maantay, Juliana; Maroko, Andrew
Abstract: Using geospatial analytical methods, this study examines the association between one aspect of the built environment, namely, the concentration of vacant and derelict land (VDL), and the prevalence of mental health disorders (using the proxy variable of mental health medication prescription rates) in Glasgow, Scotland. This study builds on our previous research, which demonstrated the spatial correspondence between the locations of VDL in Glasgow and several physical health outcomes. Numerous studies of other locales have found similar correspondence between different elements of the built environment and various health outcomes. This is the first study of its kind to look at the spatial concentration of vacant and derelict land in relation to mental health, socio-economic indicators, environmental justice, and health inequities. The findings of this study demonstrate an inequity with respect to the distribution of vacant and derelict land, as confirmed by Pearson correlations between VDL density and deprivation ( r  = .521, p  < .001). This suggests that many deprived communities are disproportionately burdened with environmental impacts and psycho-social stressors associated with this land use. Regression analyses show a significant positive association between the proportion of the population who were prescribed medication for anxiety, depression, or psychosis and the density of vacant and derelict land while adjusting for socio-demographic characteristics. This indicates that areas with higher VDL densities tend to exhibit higher rates of mental health issues. Based on these findings, strategies for constructive re-use of VDL are proposed.